ChemInform Abstract: Catalytic Enantioselective Synthesis of Atropisomeric 2‐Aryl‐4‐quinolinone Derivatives with an N—C Chiral Axis. Issue 23 (16th May 2013) - Takahashi, Isao; Morita, Fumika; Kusagaya, Shunsuke; Fukaya, Haruhiko; Kitagawa, Osamu
Abstract The 1, 4‐addition of aniline (II) to ynones (I) and (IV) followed by intramolecular Buchwald—Hartwig amination affords axially chiral quinoline derivatives (III) and (V).